1971
DOI: 10.1063/1.1665662
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Green's Function. Introduction

Abstract: Physical, analytical, and numerical properties of the lattice Green's functions for the various lattices are described. Various methods of evaluating the Green's functions, which will be developed in the subsequent papers, are mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 27 publications
0
80
0
Order By: Relevance
“…Although the integrand contains a singularity at k=0, the integral (a lattice Green's function 40 ) is convergent 41 for cubic lattices and the numerical values are given in [37]. We have obtained them via numerical integration using MATLAB.…”
Section: Second-order Fm (J = 1) At H =mentioning
confidence: 99%
“…Although the integrand contains a singularity at k=0, the integral (a lattice Green's function 40 ) is convergent 41 for cubic lattices and the numerical values are given in [37]. We have obtained them via numerical integration using MATLAB.…”
Section: Second-order Fm (J = 1) At H =mentioning
confidence: 99%
“…A lot is known about this function, in particular in the limit L i → ∞ [15,16,17]. For our purposes, however, it is sufficient to note that (i) G can be calculated at the beginning of the simulation once and for all, including the finite size effect, and that (ii) G( r = 0) is finite, even in the limit L i → ∞ (but, of course, keeping a fixed).…”
Section: Discretization Lattice Green's Function and Self-interactionmentioning
confidence: 99%
“…5 Besides, it has been shown that effective resistance is also relevant to a wide range of problems ranging from random walks on graphs, 6 the theory of harmonic functions 7 to lattice Green's functions. 8 However, not until the contribution of Klein and Randić, 1 it is revealed that the effective resistance is an intrinsic graph metric. Thanks to this important fact, people came to realize that resistance distance is a fundamental concept of graph theory and began to consider its mathematical properties as well as its applications in chemistry.…”
Section: Introductionmentioning
confidence: 99%